HUBUNGAN FUNGSI MANAJEMEN KEPALA RUANG DENGAN PENERAPAN PATIENT SAFETY DI RSUD. Dr. PIRNGADI KOTA MEDAN - Adventy Riang Bevy Gulo; Masri Saragih (UNIVERSITAS SARI MUTIARA INDONESIA, 2018)
Patient safety is the avoidance, prevention and repair of unexpected events and to overcome injuries from the health care process. This implementation is influenced by one factor only function manejemen head space. The purpose of this study is to determine the Relationship Function Manager Head Room With Application Patient Safety In Inpatient Room RSUD Dr.Pirngadi Medan City 2018. The type of this research is quantitative with correlation analytic design using cross sectional approach. The population of this study is all nurses who work in inpatient wards RSUD Dr.Pirngadi Medan as many as 249 people. Sampling technique of this research is Accidental Sampling as many as 50 people. The statistical test in this study used chi-square. Result of research indicate there is Relationship Function of Head of Room Management with Application of Patient Safety (P = 0,024, p <0,05). And it can be concluded that the better the management function of the head of space then the implementation of patient safety the better.